The importance of defining the method in particle size analysis by sieving - Adam C Fahrenholz; Leland J McKinney; C E Wurth; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 2010)
The American Society of Agricultural and Biological Engineers (ASABE) publishes a standard for identifying particle size by sieving (ASABE S319.4). However, this standard includes a number of options that allow the test to be conducted differently, and different laboratories may analyze a single sample with different results. Options include the type of sieve shaker used, the use of sieve agitators, the use of a dispersion agent, and the sieving time. A small study was conducted to examine the effect of varying these methods on the calculated geometric mean diameter by weight (dgw) and geometric standard deviation by weight (sgw). Results indicated that large differences existed depending on the methods used, with dgw varying by as much as 100 microns, and sgw varying by as much as 0.42 simply by altering one option. When compounding the differences in methods, the variations can be even larger. These discrepancies demonstrate that, for particle size analysis by sieving to be used as an effective tool, the same methodology must be used to compare samples. Additionally, the data demonstrate that unless the methods in the current standard are better defined, dgw and sgw should be used only as relative values for comparison.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Particle size; Sieving; Standard